1993
DOI: 10.1099/00221287-139-5-1077
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal halophiles (halobacteria) from two British salt mines

Abstract: Samples were taken from the Winsford salt mine in Cheshire, England, which exploits bedded deposits from the Triassic Period (195-225 million years ago, MYA) and from Boulby potash mine in Cleveland, England, which is Permian (225-270 MYA) and is mined for the mineral sylvite (KC1). Halobacteria and obligately halophilic eubacteria were isolated from several different sample types. The halobacteria were characterized by chemotaxonomic methods and most but not all were shown to be very similar but not identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 16 publications
4
91
0
1
Order By: Relevance
“…A few papers have reported the survival of archeal halophiles in dry salt over geological time scales (Norton et al, 1993;Grant et al, 1998;McGenity et al, 2000). Rothschild et al (1994) demonstrated that prokaryotes inhabiting natural wet evaporite crusts of halite and gypsum were metabolically active while inside the evaporite for at least the 10 months that it took to dry.…”
Section: Discussionmentioning
confidence: 99%
“…A few papers have reported the survival of archeal halophiles in dry salt over geological time scales (Norton et al, 1993;Grant et al, 1998;McGenity et al, 2000). Rothschild et al (1994) demonstrated that prokaryotes inhabiting natural wet evaporite crusts of halite and gypsum were metabolically active while inside the evaporite for at least the 10 months that it took to dry.…”
Section: Discussionmentioning
confidence: 99%
“…While deep subsurface evaporite deposits are known to host halophilic microbial communities (e.g. Norton et al 1993;Xiao et al 2013), a dearth of knowledge remains surrounding the diversity of subsurface microorganisms, their role in biogeochemical cycling and their association with specific evaporitic geochemistries.…”
Section: -Scientific Contributionmentioning
confidence: 99%
“…Kobayashi et al, 1992 ;Zvyagintseva & Tarasov, 1987) or salt mines (e.g. Denner et al, 1994 ;Norton et al, 1993). Abbreviations : PG, phosphatidyl glycerol ; PHB, poly-β-hydroxybutyrate ; MePGP, methylated-phosphatidyl glycerophosphate ; S-TGD, sulfated triglycosyl glycolipid ; TGD, triglycosyl glycolipid.…”
Section: Introductionmentioning
confidence: 99%